The association between hormonal variation, antioxidant status and oxidative stress in Iraqi women with endometriosis - Naji, Tamara S.; Al- Rubae’I, Salwa H. N.; Turki, Kisma M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: In the last years, Endometriosis affects up to 10 percent of reproductive aged Iraqi women. Little is known about the etiology of endometriosis in Iraqi women. Objectives: The aim of this study is to investigate the hormonal changes, antioxidant status, Coenzyme Q10 and oxidative stress in women patients with endometriosis. Patients and methods: 30 endometriotic women mean aged (31.16±5.61 year ) who were undergoing laparoscopy to participate in this study, and (n=30) healthy women volunteers mean aged (31.96±5.42 year) as control group. Results: The results in this study revealed a highly significant increased (P<0.01) in estradiol (E2), uric acid (UA) and oxidative stress (MDA). The results of the Coenzyme Q10 (CoQ10) and vitamins (A, E, β-carotene, C) showed a highly significant decreased (P<0.01) in the sera levels of patients with endometriosis as compared to control. This study showed, there was a significant negative correlation between the levels of Luteinizing Hormone (LH), Follicle Stimulating Hormones (FSH), Testosterone (Test.), E2 and vitamins, whereas a significant positive correlation was observed in UA level with concomitant increase in MDA levels. Conclusions: The results of this study concluded the increase of oxidative stress and the decrease of antioxidant vitamins and CoQ10. Thus increasing the growth and adhesion of endometrial cells in the peritoneal cavity, which will lead to increase the risk factors of endometriosis.